IDENTIFIKASI POTENSI FISIK PESISIR PANTAI WISATA BAHARI KELURAHAN TELUK KABUNG SELATAN KECAMATAN BUNGUS TELUK KABUNG KOTA PADANG - Ilhamdi Bagus Perdana; yurni suasti; ahyuni aziz (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2016)
This study aims to (1) Knowing the physical potential supporters South Teluk Kabung Village nautical tourism attractions. (2) Identify the availability of accessibility South Teluk Kabung Village. (3) Identify the availability of means of support South Teluk Kabung Village nautical tourism. (4) Identify the development of marine tourism attraction in South Teluk Kabung Village. This research is quantitative descriptive, using the techniques of data collection by observation and documentation, as well as using data from institutions Loka Resources Research and Coastal Vulnerability